Effect of Trade Unionism on Non-Academic Staff Performance in a Public Institution - Adams Lukman JIMOH; Abdulrasaq SALMAN; Idowu Jamiu YAHAYA; Idowu Afolashade ANIMASHAUN (Journal of Human Resource Management)
Purpose – Various challenges faced by non-academic personnel in Nigerian institutions, such as a lack of team spirit, inadequate salary, insufficient staff development programs, poor infrastructure, strike actions, insecurity, subpar health insurance, and limited career progression, prompted an examination of their effect on performance at the University of Ilorin. Aims(s) – This research aimed to investigate the influence of compensation structure, career development, and team spirit on the non-academic staff's performance. Design/methodology/approach – With a population of 1,600 and a sample size of 320, as established by Taro Yamane's sample size calculation, the study used a descriptive research approach. A questionnaire was used for data collection, and the Statistical Package for Social Sciences (SPSS) program was used for basic regression analysis. Findings – The results showed that non-academic staff performance at the public institutions were positively and significantly impacted by compensation structure, career growth, and team spirit. The study successfully determined the impact of trade unionism on non-academic employee performance, emphasizing the positive effects of a sound wage structure, strong team spirit, and career advancement. Limitations of the study – The fact that the results are context-specific represents a major limitation. Originality/value – The results suggested that the public institutions should prioritize and assess team spirit, along with enhancing non-academic personnel's remuneration packages. Furthermore, career advancement was identified as a key factor influencing non-academic staff performance, emphasizing the importance of providing opportunities for professional growth and promotion to motivate employees to excel and contribute to the institution's success.